2022
DOI: 10.1111/fcp.12767
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and mitochondrial dysfunction following traumatic brain injury: From mechanistic view to targeted therapeutic opportunities

Abstract: Traumatic brain injury (TBI) is one of the most prevalent causes of permanent physical and cognitive disabilities. TBI pathology results from primary insults and a multi-mechanistic biochemical process, termed as secondary brain injury. Currently, there are no pharmacological agents for definitive treatment of patients with TBI. This article is presented with the purpose of reviewing molecular mechanisms of TBI pathology, as well as potential strategies and agents against pathological pathways. In this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 448 publications
0
19
0
Order By: Relevance
“…Traumatic brain injury research remains a topic of significant research investment and numerous studies have investigated mitochondrial antioxidant molecular targets. A full discussion of these pathways is outside the scope of this review and a comprehensive discussion of animal studies of mitochondrial targets in traumatic brain injury may be found in Hakimina et al [ 93 ].…”
Section: Mitochondrial Antioxidant Interventions In Acute Neurodegene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic brain injury research remains a topic of significant research investment and numerous studies have investigated mitochondrial antioxidant molecular targets. A full discussion of these pathways is outside the scope of this review and a comprehensive discussion of animal studies of mitochondrial targets in traumatic brain injury may be found in Hakimina et al [ 93 ].…”
Section: Mitochondrial Antioxidant Interventions In Acute Neurodegene...mentioning
confidence: 99%
“…Despite this large number of preclinical trials, three clinical trials have been investigated clinically. The GSH-amplifying agent and ROS scavenger N-acetylcysteine, which has been shown to have positive effects on neuronal survival, suppressing oxidative stress, reducing apoptosis and exerting an anti-inflammatory effect in traumatic brain injury [ 93 ] was investigated in a randomized double blind placebo controlled trial in serviceman suffering mild traumatic brain injury following blast injuries in a combat zone, concluding that N-acetylcysteine improved both neuropsychological and medical symptoms following blast injury [ 94 ]. Administration of the flavonoid Enzogenol (a herbal supplement) to patients suffering mild traumatic brain injury demonstrated an improvement in cognitive symptoms compared to a placebo in a pilot randomized clinical trial [ 95 ].…”
Section: Mitochondrial Antioxidant Interventions In Acute Neurodegene...mentioning
confidence: 99%
“…We also found that antioxidant activity was suppressed by SAE, and EE could alleviate this suppression, indicating that EE improved the antioxidant system. Increased oxidative stress produces reactive oxygen species in the brain, which play a positive role in modulating the production of pro-inflammatory mediators by preventing MAPK and nuclear factor kappa B (NF-κB) activation in microglia cells [87]. Therefore, we concluded that EE alleviates the SAE-induced increase in oxidative stress and decreased antioxidant system, resulting in a decrease in pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 88%
“…Traumatic brain injury (TBI) produces an immediate mechanical injury to brain tissue followed by the secondary injury that evolves over acute, subacute, and chronic stages instigated by imbalances in neurotransmitter signal processing and connectivity, mitochondrial dysfunction, oxidative stress, and neuroinflammation (1)(2)(3)(4)(5). With moderate or severe TBI, early treatment focuses on maintaining mean arterial blood pressure (MABP) and minimizing brain swelling to mitigate intracranial hypertension.…”
Section: Introductionmentioning
confidence: 99%